Charge Density-Based Pyroelectric Vacuum Sensor - Lan Xu; Geng Huangfu; Yiping Guo; Ya Yang (Research, 2023)
A traditional thermal conductivity vacuum gauge mainly detects low pressure (the degree of vacuum) by measuring the temperature change of a filament heated by the electric current. We propose a novel pyroelectric vacuum sensor that utilizes the effect of ambient thermal conductivity on the pyroelectric effect to detect vacuum through the charge density of ferroelectric materials under radiation. The functional relationship between the charge density and low pressure is derived, which is validated in a suspended (Pb,La)(Zr,Ti,Ni)O3 (PLZTN) ferroelectric ceramic-based device. The charge density of the indium tin oxide/PLZTN/Ag device under 405 nm of 60.5 mW cm−2 radiation at low pressure reaches 4.48 μC cm−2, which is increased by about 3.0 times compared with that at atmospheric pressure. The vacuum can improve the charge density without increasing the radiation energy, confirming the important role of ambient thermal conductivity on the pyroelectric effect. This research provides a demonstration for ambient thermal conductivity effectively tuning pyroelectric performance, a theoretical basis for pyroelectric vacuum sensors, and a feasible route for further optimizing the performance of pyroelectric photoelectric devices.